THE CONCEPT OF LONG-LIFE EDUCATION IN THE STORY OF MUSA (STUDY OF TAFSIR TARBAWI ON SURAH AL-KAHFI 60-82) - Muchamad Mufid; Muchammad Iqbal Chailani (Jurnal Asy-Syukriyyah, 2024)
This research focused on the concept of long-life education in the story of Musa and Khidir surah al-Kahf: 60-82. It is a new effort to explore the values of Islamic education in this story, where previous studies still focused on character education. This research was library research with a descriptive analysis method by looking for sources from tafsir books, journals, and prior research on the story of Musa in Surah al-Kahfi: 60-82. The research results were as follows: First, tawadhu was the main principle in the concept of long-life education because each person had a specialty in mastering knowledge. Second, everyone had to motivate themselves to continuously learn, like Musa, who was enthusiastic about meeting Khidir to gain an understanding he did not yet know. Third, in seeking knowledge, a person had to always adhere to ethics towards his teacher, even at a higher level, such as Musa's ethics towards Khidr. Besides that, someone who seeked knowledge should not easily give up on the learning process even if they experience difficulties.